â€œSastraKoran Bekasâ€: Problem Komunikasi Sastra di Dunia Jurnalistik - Abdul Wachid (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
Journalistic influence, originally only at actuality and space limit of newspaper literary rubric that affect the lengthof short story, poem, and literary critic. However, because intense state hegemony on every line, include press, literarypositioning itself to participate on social problem. Journalistic still important for literary development in Indonesia, but its formulahas been questioned by literary. Therefore, literary will attract â€œcrowdâ€, by doing sublimation again, by transcend humanproblems from â€œcrowdâ€ view to human Reality.